Programming logic and design : comprehensive - Farrell, Joyce (Boston, Massachusetts : Thomson Course Technology, 2011)
With a clear writing style that is stripped of highly technical jargon, Programming Logic and Design, Introductory, Sixth Edition provides beginning programmers with a guide to developing structured program logic. The book's main goal is to introduce universal programming concepts, while enforcing good style and logical thinking along the way. The Sixth Edition will offer clearer explanations, reorganization to better reflect how programming languages are taught, increased emphasis on modularity, and two new appendices - Flowchart Symbols and Structures.
An overview of computers and logic -- Understanding structure -- The program planning process : documentation and design -- Making decisions -- Looping -- Arrays -- Using methods -- Control breaks -- Advanced array manipulation -- File handling and applications -- Object-oriented programming -- Event-driven gui programming , animation and exception handling -- System modeling with UML -- Using relational databases.
Includes index.
Keywords: LOGIC PROGRAMMING